Social Mobilization and Deliberation The Collective Action Frame as the Conclusion of a Deliberative Dialogue (2020)
The purpose of this paper is to explain the collective action of social movement organizations by means of framing processes that are understood as the result of a deliberative dialogue. To this end, the text is divided into four sections. The first section introduces the framing theory of social movement studies; the second section examines different explanations concerning the creation of a collective action framework. The third section considers the characterization of Walton and Krabbe’s deliberative dialogue (2017) as well as Fairclough and Fairclough’s practical reasoning scheme (2012) for the purpose of tracing a relationship between collective action framing and such dialogues. The last section concludes that the collective action of activists involved in the framing processes can be understood as a deliberate collective action.